Intralesional steroid and ultrasound therapy in patients with carpal tunnel syndrome (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The study aimed to compare the effects of intralesional steroid injection and ultrasound therapy for the treatment of carpal tunnel syndrome. A total 130 patients divided into 2 groups: a) One group (n=65) received intralesional corticosteroid injection along with wrist splint, exercise, naproxen sodium 500 mg tablet and omeprazole 20 mg capsule twice daily for 2 weeks; b) Another group received (n=65) ultrasound therapy (10 min/day, 3 days/week for 4 weeks) along with  Wrist splint for 4 weeks, exercises for 4 weeks, naproxen sodium 500 mg tablet and omeprazole 20 mg capsule twice daily for 2 weeks. The patients were followed-up 2 weekly for 4 weeks. The visual analogue score, symptom severity scores and functional status scores were significantly improved within each group at week 2 (p